تأثير تشميس التربة في مكافحة بعض فطور تربة البيوت البلاستكية - حسن, محمود; زيدان, رياض (Latakia University Journal -Biological Sciences Series, 2019)
جرى دراسة أثر تشميس تربة البيوت البلاستكية بتغطيتها بغطاء من البولي ايتلين الشفاف والأسود سماكة 40 ميكرون صيفاً ولمدة 40 يوماً في فطور التربة، كطريقة تعقيم بديلة للمواد الكيماوية الضارة بالبيئة والإنسان. أظهرت النتائج انخفاض أعداد الفطور الممرضة للنباتات وبشكل خاص الفطور: Fusarium.sp,Rhizoctonia.sp, Pythium.sp, Rhizopus.sp,Verticillium في حين كان تأثيرها أقل في الفطر النافع Trichoderma.sp وذلك مقارنة مع التربة غير المغطاة. تبين أيضاً تفوق معاملة التغطية بغطاء شفاف معنوياً على الغطاء الأسود في خفض أعداد الفطور وبالتالي يمكن اعتماد طريقة التعقيم الشمسي باستخدام الغطاء الشفاف كتقنية آمنة بيئياً فعالة في مكافحة فطور التربة. We carried out a study to determine the effectiveness of solarization using a 40 micron thickness of either transparent or black polyethylene cover sheets for forty days during summer. Mycosis species counts were investigated in the treated soils. Results showed a decrease in some mycosis spp., especially those of Rhizoctonia sp, Fusarium sp, Pythium sp, and Rhizopus sp, while the effect on Trichoderma sp. was very limited compared to uncovered soil. Interestingly, the effect of transparent cover sheets was significantly greater in decreasing these mycosis species compared to black sheets. We concluded that solarization is a hazard free method for human and environmentally sound substitute to the use of chemicals in sterilizing greenhouses soils to control mycosis spp.